Pengaruh Pemberian Maggot (BSF) Black Soldier Fly ke Dalam Ransum Pakan terhadap Konsumsi Pakan Ayam Petelur - Dian Afikasari; Rifa’i; Rico Angriawan; Diyah Ayu Candra; Camal Adi Maskur; Dewi Konita Safikoh (Jurnal Sains Peternakan, 2022)
This study aims to determine the administration of maggot black soldier fly (BSF) flour in the ration to the feed consumption in layers. The purpose of this research is as information material for researchers, breeders and the community in developing and utilizing maggot black soldier fly (BSF) flour which can be used as feed alternatives in order to support laying hens business. This study uses a completely randomized design (CRD) with 3 treatments and 6 replications. Treatment P0 (commercial feed), P1 ( commercial feed + maggot flour 5%), P2 (commercial feed + maggot flour 10%). Research Results Data were tested using ANOVA. Further testing to determine the differences between the groups was performed using the DUNCAN test. The lowest feed consumption values ​​were found with P2 treatment and were significantly different from P1 and P0 treatments. The average feed consumption of laying hens in one month of treatment is (grams) 120.14. 199.19; 117: 16. BSF maggots can be used instead of adding protein to the feed of spawning chickens. This is evident from the fact that the lowest feed intake was 117.16 g / head / day with P2 treatment. The results of the study were consistent with the normal feed consumption of laying hens during the spawning season, ranging from 100-120 g / head / day.